Teaching Note: Reading the Romance; Women, Patriarchy, and Popular Literature - Ohmann, Richard (Radical Teacher, 2022)
The phenomenal success of romances has naturally stirred the contempt of high culture critics, and more recently the concern of feminists, who have generally understood these narratives as promoting a kind of false consciousness, coating patriarchal values with a frosting of fantasy. The "Smithton women" appropriated romances as a pleasure strictly theirs, an antidote to the endless claims made on them by husbands and children, and a defense of "female" values like emotional sharing and (more or less) egalitarian marriage. [...]for many, regular reading of these books fed a kind of proto-feminism that made for real gains in their lives, within the limits patriarchy sets for women.